Immunohistochemical pattern of protein P21, cyclin D1 and cyclin E in endometrial hyperplasia - Brucka, Aleksandra; Bartczak, Piotr; Ratyńska, Marzena; Sporny, Stanisław (Polish Journal of Pathology, 2009)
Purpose: In our research we investigated immunohistochemical expression of cell cycle proteins protein p21, cyclin D1 and cyclin E in physiological endometrium (n = 15), hyperplastic endometrium (n = 61), and post hor-mone replacement therapy endometrium (n = 24). Material and methods: We performed immunohistochemical analysis of selected cell cycle proteins in 100 specimens of human endometrium. Results: The average immunoexpression index scores in glandular endometrial cells (GES) and stromal endometrial cells (SEC) were respectively: for p21- GES: 11.8 ±17.19%; SEC: 9.31 ±17.15%; for cyclin D1- GES: 9.25 ±18.41%; SEC: 3.22 ±11.46%; for cyclin E: GES: 26.42 ±27.47%; SEC: 4.61 ±7.90%. Statistical analysis disclosed more intense p21 glandular immunoreactivity among women with endometrial hyperplasia in comparison to other subpopulations. In the case of assessment of cyclin D1 immunoreactivity, there was no statistical correlation between analysed parameters. The average cyclin E immunoreactivity in endometrial glandular cells was significantly higher (p = 0.003) in women with endometrial hyperplasia and correlated with age. Conclusions: Intensive immunoreactivity of cyclin E in glandular cells is typical for endometrial hyperplasia and can be treated as an objective indicator of this pathological process during histopathological diagnostic procedures. Immunoreactivity index of p21 and cyclin D1 is independent of the morphological pattern of human endometrium, patients’ age and gynaecological history of patients.